PROSES SOSIALISASI DAN PENGASUHAN ANAK DI DALAM KELUARGA - Melik Budiarti (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
Parenting parents to their children is the first socialization process done by children against other people. The goal is to teach children how to be part of a better society in a broader sense as well as in the smallest of a family environment. It is inseparable from its association with the value of a child in front of his parents. Kids get the attention, or less attention will continue to grow and thrive. Children will go through the process of socialization is facilitated by social environment, parents, people who are important in a child’s life, peers and even by the media which is now irreversible existence. Need to be understood, that the theoretical concept of development as the psychoanalytic theory that center development socialization of a child lies in the development of morality and superego that when children from the age of three years. According to the theory the task of development, individual development tasks relating to social demands and the adaptation to the demands of the development of age these skills must be mastered by the individual. It will be different with the behavioristic theory, social cognitive theory, and cognitive theory and Humanistic approach also provide insights into the development of a child’s socialization. The concept of parenting is based on the assumption of various theories on the development and socialization of children directed to the development of morality, personality development and competencies for life. The development direction of guidance for parents in the upbringing of their children by the process of the elaboration of the child's personality.